3‐Hydroxyflavone enhances the toxicity of ZnO nanoparticles in vitro. Issue 9 (25th April 2018) - Luo, Yunfeng; Wu, Chaohua; Liu, Liangliang; Gong, Yu; Peng, Shengming; Xie, Yixi; Cao, Yi
Abstract: It is recently shown that flavonoids might reduce the toxicity of nanoparticles (NPs) due to their antioxidative properties. In this study, the influence of 3‐hydroxyflavone (H3) on the toxicity of ZnO NPs was investigated. H3 increased hydrodynamic size, polydispersity index and absolute value of the zeta potential of ZnO NPs, which indicated that H3 could influence the colloidal aspects of NPs. Surprisingly, H3 markedly decreased the initial concentration of ZnO NPs required to induce cytotoxicity to Caco‐2, HepG2, THP‐1 and human umbilical vein endothelial cells, which suggested that H3 could promote the toxicity of ZnO NPs to both cancerous and normal cells. For comparison, 6‐hydroxyflavone did not show this effect. H3 remarkably increased cellular Zn elements and intracellular Zn ions in HepG2 cells following ZnO NP exposure, and co‐exposure to H3 and NPs induced a relatively higher intracellular reactive oxygen species. Exposure to ZnO NPs at 3 hours induced the expression of endoplasmic reticulum stress markers DDIT3 and XBP‐1 s, which was suppressed by H3. The expression of apoptotic genes BAX and CASP3 was significantly induced by ZnO NP exposure after 3 and 5 hours, respectively, and H3 further significantly promoted CASP3 expression at 5 hours. In combination, the results from this study suggested that H3 affected colloidal stability of ZnO NPs, promoted the interactions between NPs and cells, and altered the NP‐induced endoplasmic reticulum stress–apoptosis signaling pathway, which finally enhanced the cytotoxicity of ZnO NPs. Abstract : Recent study suggested that phytochemicals might reduce the toxicity of nanoparticles (NPs). The present study investigated the combined toxicity of ZnO NPs and 3‐hydroxyflavone (H3). H3 influenced the colloidal stability of ZnO NPs, and surprisingly enhanced the cytotoxicity of NPs to both cancerous and normal cells. Co‐exposure to ZnO NPs and H3 increased NP–cell interactions, induced a relatively higher level of reactive oxygen species and altered the endoplasmic reticulum stress–apoptosis pathway, which could be responsible for the combined toxicity.